(untitled) (Research, Society and Development, 2021)
The act of playing allows children to invent, create and imagine making the school environment a more interactive space for their learning. The article aims to understand the importance of pedagogical practices and the relevance of play as a methodological way of teaching that contributes to children’s learning. Thus, to guide this study, an investigation was carried out with six collaborators working in the first three years of Elementary School, in the 2020 school year, at the Lourdes Maria de Lima Municipal School, located in the city of Jauru – MT. The methodology was based on a case study with a qualitative approach and descriptive research. The data collection instrument was the online questionnaire. The article had as theoretical support: Freire, Kishimoto and Vygotsky among others. The results show that the teachers understand the importance of play in the teaching-learning process as a methodological way that contributes to the development of the student.